Defect Study of MgO-CaO Material Doped with CeO2 - Han Zhang; Huizhong Zhao; Jinfeng Chen; Jingjie Li; Jun Yu; Jianhua Nie (Advances in Materials Science and Engineering)
MgO-CaO refractories were prepared using analytical reagent chemicals of Ca(OH)2 and Mg(OH)2 as starting materials and CeO2 as dopant, then sintered at 1650°C for 3 h. The effect of CeO2 powders on the defect of MgO-CaO refractories was investigated. The sample characterizations were analyzed by the techniques of XRD and SEM. According to the results, with the addition of CeO2, the lattice constant of CaO increased, and the bulk density of the samples increased while apparent porosity decreased. The densification of MgO-CaO refractories was promoted obviously. In the sintering process, MgO grains grew faster than CaO, pores at the MgO-CaO grain boundaries decreased while pores in the MgO grains increased gradually, and no pores were observed in the CaO grains. The nature of the CeO2 promoting densification lies in the substitution and solution with CaO. Ce4+ approaches into CaO lattices, which enlarges the vacancy concentration of Ca2+ and accelerates the diffusion of Ca2+.